Multiproperty Polyethylenimine-Caged Platinum Nanoclusters Promote Apoptosis of Osteosarcoma Cells via Regulating the BAX-Bcl-2/Caspase-3/PARP Axis - Wang, Jialin; Zhang, Mengjun; Huang, Xin; Yue, Haodi (Molecular pharmaceutics, 2023)
Osteosarcoma, a prevalent primary bone cancer in children, exhibits a poor prognosis due to the high prevalence of drug resistance. The objective of this study was to investigate the potential of fluorescent ultrafine polyethylenimine-coated caged platinum nanoclusters (PEI-Pt NCs) as an antitumor agent in osteosarcoma. The primary focus of this study involved the utilization of osteosarcoma cells (U2-OS and MG-63) and normal control cells (hBMSC) as the primary subjects of investigation. The capacity of PEI-Pt NCs to enter osteosarcoma cells was observed through the implementation of confocal microscopy. The impact of PEI-Pt NCs on migration and proliferation was assessed through the utilization of various methodologies, including the CCK8 assay, K i-67 immunofluorescence, clone formation assay, transwell assay, and wound healing assay. Furthermore, the influence of PEI-Pt NCs on apoptosis and its underlying mechanism was explored through the implementation of flow cytometry and Western blotting techniques. The PEI-Pt NCs demonstrated the capability to enter osteosarcoma cells, including the nucleus, while also exhibiting fluorescent labeling properties. Furthermore, the PEI-Pt NCs effectively impeded the migration and proliferation of osteosarcoma cells. Additionally, the PEI-Pt NCs facilitated apoptosis by modulating the BAX-Bcl-2/Caspase 3/PARP axis. The novel nanomaterial PEI-Pt NCs possess diverse advantageous capabilities, including the ability to impede cell proliferation and migration, as well as the capacity to modulate the BAX-Bcl-2/Caspase 3/PARP axis, thereby promoting cell apoptosis. Consequently, this nanomaterial exhibits promising potential in addressing the issue of inadequate platinum-based treatment for osteosarcoma.